2015
DOI: 10.1111/jdv.13445
|View full text |Cite
|
Sign up to set email alerts
|

Treatment monitoring of 0.5% 5‐fluorouracil and 10% salicylic acid in clinical and subclinical actinic keratoses with the combination of optical coherence tomography and reflectance confocal microscopy

Abstract: Evaluation of AK and subclinical AK by RCM and HD-OCT showed objective improvement after treatment with 5-fluorouracil and 10% salicylic acid. These methods allowed the study of dynamic changes in the tissue at a subclinical level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 26 publications
4
37
0
1
Order By: Relevance
“…Performing biopsies on the arms results in less aesthetic impact for participants. Previous studies have demonstrated the applicability of RCM in monitoring AK treatment on the face, scalp and forearms with similar results …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Performing biopsies on the arms results in less aesthetic impact for participants. Previous studies have demonstrated the applicability of RCM in monitoring AK treatment on the face, scalp and forearms with similar results …”
Section: Discussionsupporting
confidence: 58%
“…also emphasized the importance of RCM in therapeutic evaluation of AKs undergoing photodynamic therapy. Malvehy et al …”
Section: Discussionmentioning
confidence: 99%
“…Two small (case series) studies using RCM recently determined that field-directed 5-FU 0.5%/salicylic acid 10% for up to 6 weeks of treatment was effective not only for investigating the transitioning of clinically visible lesions from a higher to lower grade, but also for clearing sub-clinical lesions after field-directed treatment [21, 22]. The results from the RCM sub-study in a group of 30 patients from the current study will be published separately.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 By increasing treatment duration from 6 to 12 weeks and extending the posttreatment observation period to 12 weeks, the current study adds important data concerning the sustainability of the response to 5-FU 0.5%/salicylic acid 10%. 8,12 By increasing treatment duration from 6 to 12 weeks and extending the posttreatment observation period to 12 weeks, the current study adds important data concerning the sustainability of the response to 5-FU 0.5%/salicylic acid 10%.…”
Section: Discussionmentioning
confidence: 91%
“…4,11 A recent study that examined the correlation between RCM and histopathology for the detection of keratinocyte atypia, a key parameter for AK grading and characterization, reported similar detection rates for both RCM and histopathology, and high concordance between the two techniques in terms of the grading of keratinocyte morphology. 12 A previous Phase III study investigating the efficacy and safety of topical 5-FU 0.5%/salicylic acid 10% as field-directed treatment for clinical AK lesions (Grade I/II) over a 25 cm 2 area of skin, showed significantly higher rates of complete lesion clearance for active treatment, compared with vehicle. 12 A previous Phase III study investigating the efficacy and safety of topical 5-FU 0.5%/salicylic acid 10% as field-directed treatment for clinical AK lesions (Grade I/II) over a 25 cm 2 area of skin, showed significantly higher rates of complete lesion clearance for active treatment, compared with vehicle.…”
Section: Introductionmentioning
confidence: 97%